Dampak Karakteristik Biografis dan Fasilitas Kerja Terhadap Tugas Pegawai (Study Kasus Dinas Koperasi, Ukm, Perindustrian Dan Perdagangan Kabupaten Solok) - Restika Ayu Nengsih; Nurhayati Nurhayati; Seflidiana Roza (Universitas 45 Surabaya, 2023)
This research was conducted within the Department of Cooperatives, SMEs, Industry and Trade, Solok Regency. The purpose of this research is to find out how big the impact of biographical characteristics and work facilities on the duties of employees within the Department of Cooperatives, SMEs, Industry and Trade, Solok Regency. In this study, the population was employees in the Department of Cooperatives, SMEs, Industry and Trade of Solok Regency totaling 61 people. By using purposive sampling, a sample of 35 people was obtained. The data collection technique used is by using a questionnaire or questionnaire. Based on multiple linear regression analysis of the variable biographical characteristics and work facilities have an effect on employee duties. Y= 20.55+ 0.555 X1 + 0.366 X2. From the t-test, it was found that the variable X1 Biographical Characteristics had a significant effect on employee duties with a variable value of 1.804 > ttable 1.693 and a significant value level of 0.008 <a 0.05. Variable X2 work facilities has a significant effect on employee duties with a value of 2,274 > t table 1,693 and a significant value of 0.010 < 0.05. From the f test conducted, it is found that the Biographical Characteristics and work facilities have a simultaneous effect on employee duties. Fcount is 6.148 > Ftable 3.280 and with this the significance is 0.006 < 0.05.